Desarrollo de un sistema de indicadores de sostenibilidad ambiental para la conservación del páramo Ashigua, parroquia Mulaló, cantón Latacunga, provincia de Cotopaxi. - Escobar Freire, Jessica Del Rocio (2022)
The research project was developed in the “Ashigua” moor of the Mulaló parish, Latacunga canton, Cotopaxi Province, with the purpose of developing a system of environmental sustainability indicators for the moor conservation of the aforementioned sector, which is broken down in three important aspects: the socio-environmental state diagnosis of the moor, to indicators of environmental sustainability system, as a tool that allows guiding the population on the care importance and moor preservation, and the elaboration of a community development agenda for the measures development for the conservation and moor preservation. The methodology used was carried out in two phases: qualitatively through a bibliographic review on topics related to environmental sustainability, sustainable management and the study area description, the use of geographic information tools (GIS) and quantitative way, the tabulation of the survey, which resulted in the development of indicators according to the moor needs, allowing to provide solutions, as well as the method of Andean Community Planning (PAC), for the agenda development, techniques such as participatory workshops with environmental, social, cultural and economic aspects were applied, that is why the agenda was prepared where objectives are proposed with their respective goals to achieve sustainable development and improvement of the quality of life of current and future generations. . The main results obtained showed that the population consists of 90 inhabitants in the respective study area through the surveys it was determined that there is a lack of knowledge on issues such as climate change, sustainable management for the paramo. In addition, it is important that the inhabitants of the Ashigua community and the competent authorities become aware of the issue because serious problems harm human well-being and the environment.